Genitive Case in Kurdish and English Language - Aziz, Aryan Sdiq; Ghairb, Nali Adham; Karim, Chia Karim; Hama Gharib, Bahra Salam; Hama Amin, Tanya Ismail; Abdalla, Shabaz (Raden Intan State Islamic University of Lampung, Indonesia, 2024)
Linguistic and grammatical correctness, both in their production and when they are categorized under specialized grammar, involve numerous features unique to each language and the technical intricacies of its grammar. One such feature encompasses processes related to the genitive case, encompassing the nuanced details of genitive attribution, possession, indicators of possession, and the presence or absence of these indicators in their respective contexts. This research delves into the Genitive Case in Kurdish and English, elucidating their positions, commonalities, and distinctions. The methodology employed throughout this study is primarily analytical and comparative, wherein initial observations and insights about the phenomenon are presented, followed by a thorough analysis and demonstration of the genitive case in both Kurdish and English grammar.